Decency in the digital era: Exploring preferences of transit riding among females in different life stages - Bing Yan; Chen Wan; Yinli Chen; Chengcheng Yu; Lu Huang (Journal of Public Transportation)
Investigating women’s public transit usage intentions (TUIs) is essential for enhancing service quality and ensuring female passengers’ travel rights. However, for women with distinct socioeconomic backgrounds, the heterogeneity of factors impacting their TUIs is not thoroughly explored. In this research, we conducted a survey in Hangzhou, China, collected 1294 valid questionnaires from women, and employed the Latent Class Analysis method (LCA) and Ordered Logit Model (OLM) to identify the distinct determinants of TUIs among different female groups. The findings reveal that: (1) Retired elderly women, who are less able to walk, require more spatial accessibility of transit services and the availability to reduce their first/last-mile walking and waiting time; (2) Middle-aged and high-income groups prioritize comfort, punctuality, and safety, particularly favoring the provision of ladies-only seating areas; (3) Young and student groups' transit usage is predominantly influenced by fare policies. By incorporating digital technologies, customized operational strategies such as real-time transit information systems, surveillance cameras, tiered discount schemes, and digital payment services are recommended to improve the TUIs among different female groups. Our work contributes to creating a more female-friendly public transit environment.